2021
DOI: 10.1002/hed.26888
|View full text |Cite
|
Sign up to set email alerts
|

miR‐29a‐3p promotes migration and invasion in ameloblastoma via Wnt/β‐catenin signaling by targeting catenin beta interacting protein 1

Abstract: Background: Ameloblastoma (AB) is a common epithelial odontogenic tumor. The Wnt/β-catenin pathway has been found to be related to AB invasion. Methods:The alteration expression of microRNAs (miRNAs) and messenger RNAs (mRNAs) was performed by miRNA and mRNA microarray analysis and validated by quantitative real-time polymerase chain reaction (RT-PCR). The effects of miR-29a-3p on migration and invasion in AB cells were evaluated by a transwell assay. Bioinformatic prediction was conducted using the miRSystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The RAF1-MEK/ERK-ARL4C axis may function in cooperation with the BRAFV600E-MEK/ERK pathway to promote ameloblastoma development [50]. The microRNA miR-29a-3p promotes migration and invasion in ameloblastoma via Wnt/β-catenin signaling by targeting catenin beta interacting protein 1 [51]. The upfront treatment with BRAF inhibitors resulting in substantial tumor regression has enabled non-mutilating complete surgical removal, ad integrum bone regeneration, and organ preservation.…”
Section: Recent Advancesmentioning
confidence: 99%
“…The RAF1-MEK/ERK-ARL4C axis may function in cooperation with the BRAFV600E-MEK/ERK pathway to promote ameloblastoma development [50]. The microRNA miR-29a-3p promotes migration and invasion in ameloblastoma via Wnt/β-catenin signaling by targeting catenin beta interacting protein 1 [51]. The upfront treatment with BRAF inhibitors resulting in substantial tumor regression has enabled non-mutilating complete surgical removal, ad integrum bone regeneration, and organ preservation.…”
Section: Recent Advancesmentioning
confidence: 99%
“…miR-29a-3p directly targets the Wnt/β-catenin signaling pathway in several types of cancer including ameloblastoma ( 39 ) and gastric cancer ( 8 ). To further investigate the underlying mechanisms involved, the association between miR-29a-3p and Wnt/β-catenin signaling pathway in NSCLC was further examined next.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs could stimulate early-stage NSCLC progression by simultaneously stimulating Wnt/β-catenin signaling ( 6 ). Moreover, it has been reported that miR-29a-3p regulates the migration and invasion in ameloblastoma via the Wnt/β-catenin pathway ( 39 ). The Wnt/β-catenin pathway was inactivated in a miR-29a-3p-dependent manner in GC cells ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that miR-29a-3p levels in tissues were higher than normal in ameloblastoma. Additional research showed that miR-29a-3p directly targets the β-catenin interacting protein 1 (CTNNBIP1), which negatively regulated the activity of the Wnt/-βcatenin pathway and facilitates cell migration and invasion [ 72 ]. Sikder et al discovered PC4, a transcriptional coactivator, as a target of miR-29a-3p in breast cancer, which led to tumor growth both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%